Spatial econometric analysis with applications to regional macroeconomic dynamics - Formánek, Tomáš; Cahlík, Tomáš, 1956-; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2019)
Regional macroeconomic processes may not be properly analyzed without accounting for their spatial nature: geographic distances and interactions between neighbors. State level and regional macroeconomic policy actions should be prepared, implemented and evaluated while accounting for the spatial nature of their effects: positive or negative spillovers may influence the desired outcome. Spatial econometrics is a versatile tool for a broad range of quantitative analyses performed with geo-coded (spatially defined) data. Over the last few years, both cross-sectional and panel data methods of spatial analysis have gained considerable attention in literature. While both types of data provide valuable insight and improve relevancy of quantitative analyses, spatial panels often bring useful advantages over cross-sectional spatial data in terms of tackling the temporal aspects of (macroeconomic or other) dynamics as well as by allowing to account for unit's individual effects.This contribution to spatial analysis provides both methodological background and empirical applications of spatial econometric methods. The theoretically and methodologically focused chapters contain a comparative summary of estimation methods, corresponding tests and model interpretations. In contrast with most publications in the field, great emphasis is given to model robustness evaluation with respect to possible changes in the underlying spatial structure (both conceptual and parametric differences in spatial definitions are discussed). The empirical/application part of this contribution is focused on regional dynamics in macroeconomic processes within selected EU countries, with major emphasis on the Czech Republic and its neighbors.
Vedoucí práce
Habilitační práce (doc.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2019
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2019
Způsob přístupu: Internet